Comparison of Life Table Characteristics of Myzus Persicae (Sulzer) (Aphididae: Hemiptera) Reared for Two Successive Generations on Cabbage (Brassica oleracea L. var. capitata) under an Ambient Condition in Pokhara, Nepal - Baral, S.; Thapa, R.B.; Jha, R.K.; Joshi, S.L.; Aryal, S. (Journal of the Plant Protection Society, 2020)
Abstract available with the full text.